Utilization of lignin: A sustainable and eco-friendly approach. Issue 1 (February 2020) - Kumar, Adarsh; Anushree; Kumar, Jitendra; Bhaskar, Thallada
Abstract: The use of renewable carbon sources as a substitute for fossil resources is an extensively essential and fascinating research area for addressing the current issues related to climate and future fuel requirements. The utilization of lignocellulosic biomasses as a source for renewable fuel/chemicals/mesoporous biochar derivative is gaining considerable attention due to the neutral carbon cycle. The cellulose and hemicellulose are highly utilized components of biomass, and on the other hand, lignin is a plentiful, under-utilized component of the lignocellulosic biomass in 2G ethanol and paper industry. Significant researchers have contributed towards lignin valorization, with a central goal of the production and upgradation of phenolic, unstable, acidic and oxygen-containing bio-oil to valuable chemicals or fuel grade hydrocarbons. This review is aimed to present the lignin valorization potential from pretreatment of biomass as an initial step to the final process, i.e., lignin bio-oil upgradation with mechanistic pathways. The review offers the source, structure, composition of various lignocellulosic biomasses, followed by a discussion of various pre-treatment techniques for biomass depolymerization. Different thermochemical approaches for bio-oil production from dry and wet biomasses are highlighted with emphasis on pyrolysis and liquefaction. The physical, chemical properties of lignin bio-oil and different upgradation methods for bio-oil as well as its model compounds are thoroughly discussed. It also addresses the related activity, selectivity, stability of numerous catalysts with reaction pathways and kinetics in a broad manner. The challenges and future research opportunities of lignin valorization are discussed in an attempt to place lignin as a feedstock for the generation of valuable chemical and fuel grade hydrocarbons. Graphical abstract: Image 1 Highlights: Lignin is an unused component in 2G ethanol and pulp & paper industry and has 10–25% wt % of biomass. Bio-oil has low pH, high, high density, high oxygen content, and low heating value. Catalytic cracking, steam reforming, and HDO are major pathways for upgradation. Design of catalyst for selective cleavage of bonds for functional compounds required for economic viability.